2004
DOI: 10.1128/mmbr.68.2.345-361.2004
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Responses to Microgravity and Other Low-Shear Environments

Abstract: Microbial adaptation to environmental stimuli is essential for survival. While several of these stimuli have been studied in detail, recent studies have demonstrated an important role for a novel environmental parameter in which microgravity and the low fluid shear dynamics associated with microgravity globally regulate microbial gene expression, physiology, and pathogenesis. In addition to analyzing fundamental questions about microbial responses to spaceflight, these studies have demonstrated important appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
356
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(361 citation statements)
references
References 90 publications
(227 reference statements)
2
356
0
3
Order By: Relevance
“…As environmental changes induce and select for physiological, metabolic and/or genetic variations in microorganisms (Foster, 2007), it is envisioned that such adaptations will also likely occur under space flight conditions. Indeed, numerous in-flight studies have confirmed that space flight can have a pronounced effect on a variety of microbial parameters including changes in microbial proliferation rate, cell morphology, cell physiology, cell metabolism, genetic transfer among cells and viral reactivation within the cells (reviewed in Leys et al, 2004;Nickerson et al, 2004;Nicholson et al, 2005;Klaus and Howard, 2006). However, previous studies have also shown that the results from space flight and space flight analog experiments can radically differ when using different bacteria or when using the same bacterium but different culture media Leff, 2004, 2006;Benoit and Klaus, 2007;Wilson et al, 2008;Leys et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…As environmental changes induce and select for physiological, metabolic and/or genetic variations in microorganisms (Foster, 2007), it is envisioned that such adaptations will also likely occur under space flight conditions. Indeed, numerous in-flight studies have confirmed that space flight can have a pronounced effect on a variety of microbial parameters including changes in microbial proliferation rate, cell morphology, cell physiology, cell metabolism, genetic transfer among cells and viral reactivation within the cells (reviewed in Leys et al, 2004;Nickerson et al, 2004;Nicholson et al, 2005;Klaus and Howard, 2006). However, previous studies have also shown that the results from space flight and space flight analog experiments can radically differ when using different bacteria or when using the same bacterium but different culture media Leff, 2004, 2006;Benoit and Klaus, 2007;Wilson et al, 2008;Leys et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…B. subtilis has also been found to weather granite (Song et al 2007) in order to extract essential minerals to live. Understanding its behaviour in micro-gravity is of high importance as it has been found previously as a common contaminant on the ISS (Nickerson et al 2004). C. metallidurans CH34 is a Gram-negative, motile, nonspore forming bacterium and a model organism to study metal resistance and tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial biofilms are important for biomining as one of the most commonly used industrial methods for terrestrial biomining, heap leaching reactors, require the mining microorganisms to grow in biofilms (Rawlings & Johnson 2007). Microbial biofilms have been found to behave quite differently in low gravity and other low-shear environments than is usually expected from them on Earth (see Nickerson et al 2004 for a review). Differences in biofilm formation in space have been observed in organisms that have been studied from the medical perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms, however, have been generally regarded as too small and intracellularly homogeneous for gravity to have an impact on their physiology (Pollard, 1965). In recent years, evidence to the contrary has been steadily mounting (Nickerson et al, 2004). Escherichia coli (ThĂ©venet et al, 1996;Klaus et al, 1997), Bacillus subtilis (Mennigmann and Lange, 1986) and Salmonella typhimurium (Mattoni, 1968) cultures have all displayed altered growth characteristics during space flight.…”
Section: Introductionmentioning
confidence: 99%